Papillary Dermal Elastolysis Secondary to Combination Nivolumab and Cabiralizumab Therapy: Histiocytes and Dermal Mucin as Clues to the Diagnosis. (October 2021) - Yin, Lu; Criscito, Maressa C.; Stokar, Evan; Siolas, Despina; Haimovic, Adele; Lo Sicco, Kristen; Brinster, Nooshin K.
Abstract : Abstract: Papillary dermal elastolysis has been described in the setting of experimental combination nivolumab and cabiralizumab immunotherapy. We report a third patient with distinctive, generalized atrophic macules that developed after a morbilliform eruption during a clinical trial for treatment of metastatic pancreatic adenocarcinoma. Histopathological findings demonstrated diminished elastic fibers in the papillary dermis, associated with a histiocyte-rich infiltrate and increased dermal mucin, features that should clue the dermatopathologist to this condition.